Analisis Potensi Energi Angin sebagai PLTB di Pantai Watu Ulo Jember Menggunakan data BMKG - Ardiana, Jessica Dwi Putri; ., Yusardhi; ., Sudarti (CV. ITTC INDONESIA, 2023)
This research aims to analyze the potential of wind energy as a resource for Wind Turbine Power Plants (PLTB) in the coastal area of Watu Ulo Beach, Jember. The research adopts a literature review method, utilizing data provided by the Meteorology, Climatology, and Geophysics Agency (BMKG). BMKG data serves as the primary source for this analysis, providing a robust foundation to evaluate the potential of PLTB. The study also focuses on the availability of state-of-the-art technology to optimize the utilization of wind energy, assessing its suitability for the region's characteristics. The research findings are expected to provide a comprehensive overview of the PLTB potential in Watu Ulo Beach, Jember, serving as a basis for the development of sustainable energy infrastructure in coastal areas. The conclusions drawn from this literature review are anticipated to serve as a reference for further research and the implementation of sustainable PLTB projects in the region.